2024
DOI: 10.1021/jacs.3c11632
|View full text |Cite
|
Sign up to set email alerts
|

Pd–Mn/NC Dual Single-Atomic Sites with Hollow Mesopores for the Highly Efficient Semihydrogenation of Phenylacetylene

Huan Liu,
Peng Zhu,
Da Yang
et al.

Abstract: The direct pyrolysis of metal-zeolite imidazolate frameworks (M-ZIFs) has been widely recognized as the predominant approach for synthesizing atomically dispersed metal−nitrogen-carbon single-atom catalysts (M/NC-SACs), which have exhibited exceptional activity and selectivity in the semihydrogenation of acetylene. However, due to weak adsorption of reactants on the single site and restricted molecular diffusion, the semihydrogenation of large organic molecules (e.g., phenylacetylene) was greatly limited for M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 55 publications
(74 reference statements)
0
0
0
Order By: Relevance
“…have shown notable advantages in terms of stability and recoverability, which suffer from the limitations of low activity, poor selectivity, and a high reaction temperature (Figure b). As an emerging heterogeneous catalyst, single-atom catalysts (SACs) have become an important platform that bridge heterogeneous catalysis and homogeneous catalysis. In recent years, SACs have been successfully applied in various organic reactions, achieving comparable activity and selectivity to homogeneous catalysts. Fortunately, as the non-noble metal, Co-SACs are widely recognized as efficient catalysts of dehydrogenation and hydrogenation processes. Li et al have reported highly active Co 1 /V 2 O 5 in the dehydrogenative coupling reaction of alcohols with amines to imines . Additionally, the hydrogenation of nitrobenzene to aniline can be efficiently catalyzed by atomically dispersed Co 1 /NPC, as demonstrated by Cao et al Co-SACs have never been applied for the N -alkylation of amines with alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…have shown notable advantages in terms of stability and recoverability, which suffer from the limitations of low activity, poor selectivity, and a high reaction temperature (Figure b). As an emerging heterogeneous catalyst, single-atom catalysts (SACs) have become an important platform that bridge heterogeneous catalysis and homogeneous catalysis. In recent years, SACs have been successfully applied in various organic reactions, achieving comparable activity and selectivity to homogeneous catalysts. Fortunately, as the non-noble metal, Co-SACs are widely recognized as efficient catalysts of dehydrogenation and hydrogenation processes. Li et al have reported highly active Co 1 /V 2 O 5 in the dehydrogenative coupling reaction of alcohols with amines to imines . Additionally, the hydrogenation of nitrobenzene to aniline can be efficiently catalyzed by atomically dispersed Co 1 /NPC, as demonstrated by Cao et al Co-SACs have never been applied for the N -alkylation of amines with alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Single-atom catalysts (SACs), a recently emerging type of heterogeneous catalysts that feature uniform and well-defined structures, have pushed the boundary of heterogeneous catalysis. The active metal species are atomically dispersed and anchored well by the coordination atoms in the first shell, forming the “metal–1st shell coordination atom–2nd shell coordination atom” moieties within the supports. Generally, nonmetallic elements serve as the coordination atoms in the first and second shells, i.e., carbon (C), oxygen (O), nitrogen (N), and sulfur (S) atoms . The interactions between active metal species and the coordination atoms can influence the geometric structures and electronic states of central metal species and thus govern the catalytic performance of SACs toward various reactions, guided by the theoretical calculations. , Thus, tuning the first- and second-shell coordination atoms of active metal atoms in SACs is a powerful strategy for designing high-performance SACs. Nowadays, a lot of attention has been focused on the first-shell coordination atoms, and the as-designed SACs offer unrivaled selectivity and activity for a certain number of electrochemical and photochemical reactions. , It is well expected that highly active SACs for the hydrogenation of HNBs can be achieved via precisely tuning the second-shell coordination atoms.…”
mentioning
confidence: 99%